Tissue preservation with mass spectroscopic analysis: Implications for cancer diagnostics - Hall, O. Morgan (Cancer Biol Ther, 2018)
Surgical intervention is a common treatment modality for localized cancer. Post-operative analysis involves evaluation of surgical margins to assess whether all malignant tissue has been resected because positive surgical margins lead to a greater likelihood of recurrence. Secondary treatments are utilized to minimize the negative effects of positive surgical margins. Recently, in Science Translational Medicine, Zhang et al describe a new mass spectroscopic technique that could potentially decrease the likelihood of positive surgical margins. Their nondestructive in vivo tissue sampling leads to a highly accurate and rapid cancer diagnosis with great precision between healthy and malignant tissue. This new tool has the potential to improve surgical margins and accelerate cancer diagnostics by analyzing biomolecular signatures of various tissues and diseases.